Navigator‐3, a modulator of cell migration, may act as a suppressor of breast cancer progression. Issue 3 (12th February 2015) - Cohen‐Dvashi, Hadas; Ben‐Chetrit, Nir; Russell, Roslin; Carvalho, Silvia; Lauriola, Mattia; Nisani, Sophia; Mancini, Maicol; Nataraj, Nishanth; Kedmi, Merav; Roth, Lee; Köstler, Wolfgang; Zeisel, Amit; et al.
Abstract Dissemination of primary tumor cells depends on migratory and invasive attributes. Here, we identify Navigator‐3 (NAV3), a gene frequently mutated or deleted in human tumors, as a regulator of epithelial migration and invasion. Following induction by growth factors, NAV3 localizes to the plus ends of microtubules and enhances their polarized growth. Accordingly, NAV3 depletion trimmed microtubule growth, prolonged growth factor signaling, prevented apoptosis and enhanced random cell migration. Mathematical modeling suggested that NAV3‐depleted cells acquire an advantage in terms of the way they explore their environment. In animal models, silencing NAV3 increased metastasis, whereas ectopic expression of the wild‐type form, unlike expression of two, relatively unstable oncogenic mutants from human tumors, inhibited metastasis. Congruently, analyses of > 2, 500 breast and lung cancer patients associated low NAV3 with shorter survival. We propose that NAV3 inhibits breast cancer progression by regulating microtubule dynamics, biasing directionally persistent rather than random migration, and inhibiting locomotion of initiated cells.